Study of Stone Period Monuments (On the Example of the Medium Zerafshan OAS) - S T Mirsoatova (Procedia of Social Sciences and Humanities, 2022)
This article is devoted to the history of the discovery of one of the archaeological cultures of the Neolithic era - Sazagan culture, studied in the territory of Central Zarafshan and notes the special services of the M. Jurakulov. The Sazagan culture was in cultural contact with the cultural communities of Kaltaminar, Central Fergana, Ustyurt, which were studied in Uzbekistan and Gissar in Tajikistan. At the same time, the Middle Zarafshan region has been inhabited by people since the Paleolithic era, and later periods, in particular the Sazagan Neolithic communities, were also interpreted as belonging to the local indigenous population due to the specifics of their material culture.